Peran Remaja Islam Masjid dalam Meningkatkan Efektivitas Masjid Baitul Makmur Desa Sinar Pagi Kaur Selatan - Ceria Febiola; Dwi Rizki; Jeni Valestiani; Anggi Junia Restika; Adella Fitriyani; Raju Putra Pratama; Sundari Elisa Lestari; Rike Amelia; Elpita Pitriani; Rengga Alfichar Putra; Dayun Riyadi (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
Real Work From Home Lectures Based on Community Empowerment is a routine program from the Fatmawati Sukarno Bengkulu State Islamic University which aims to develop students' insight, knowledge, skills, values and attitudes in society and be able to contribute to the surrounding community. The activity method is carried out by means of workshops, lectures and questions and answers which will be held from June 21 2024 to August 6 2024. The scope of this activity is carried out in Kaur Regency which has a village with active youth mosque activities. The results of this activity show an increase in the knowledge and skills of mosque youth in protecting the community in accordance with the program themes in their respective villages which consist of English, reading and writing the Koran, social media Facebook, promiscuity and dating, street vendors, Islamic families, e-commerce, creative economy, speaking English, usury, monotheism of the younger generation, mathematics teaching aids for children.